2016
DOI: 10.1002/chem.201600213
|View full text |Cite
|
Sign up to set email alerts
|

Dipolar Photosystems: Engineering Oriented Push–Pull Components into Double‐ and Triple‐Channel Surface Architectures

Abstract: Push-pull aromatics are not popular as optoelectronic materials because their supramolecular organization is difficult to control. However, recent progress with synthetic methods has suggested that the directional integration of push-pull components into multicomponent photosystems should become possible. In this study, we report the design, synthesis, and evaluation of double- or triple-channel architectures that contain π stacks with push-pull components in parallel or mixed orientation. Moreover, the parall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 117 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…However, the availability of reloaded CPDs such as 10 was also of practical interest because increasing uptake activity of monomers 3 – 5 with increasing tension suggested that similar increases in activity could be achieved on the level of the intrinsically much more active polymers. Because of much experience with orthogonal dynamic covalent chemistry in different contexts,[15][17] hydrazone exchange was initially envisioned for sidechain modification of CPDs. However, the results were not convincing (not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the availability of reloaded CPDs such as 10 was also of practical interest because increasing uptake activity of monomers 3 – 5 with increasing tension suggested that similar increases in activity could be achieved on the level of the intrinsically much more active polymers. Because of much experience with orthogonal dynamic covalent chemistry in different contexts,[15][17] hydrazone exchange was initially envisioned for sidechain modification of CPDs. However, the results were not convincing (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Sidechain modification of polymers is of general interest to avoid tedious optimization of polymerization conditions with every structural modification and to produce comparable functional systems with identical scaffold [4 – 6][12] [15 – 21]. Synthetic strategies that in part have been applied previously to synthetic transport systems include the formation of hydrazones,[4][15][16] sulfonium cations,[6] boronate esters,[17] amides,[12] thioesters,[18] disulfides,[19] diselenides,[20] triazoles,[5][21] and so on. In the following, we introduce a general method for sidechain modification of CPDs to secure synthetic access to comparable systems.…”
Section: Introductionmentioning
confidence: 99%
“…2 Another useful point of D-p-A molecules is the large dipole moment generated in the molecule, which can be used to facilitate a charge separation process upon molecular excitation by resisting against the large exciton binding energy. 3,4 A p-type organic semiconductor showing a carrier mobility up to 20 cm 2 V À1 s À1 has been attained by polymer carrying D and A substituents, and an n-type organic semiconductor of nearly 10 cm 2 V À1 s À1 as well. 5 The performances of those organic semiconductors are determined mainly by two factors of organic molecules themselves and their mutual arrangement in the nm-size devices.…”
Section: Introductionmentioning
confidence: 99%
“…PMI recently appeared as an important dye and a versatile building block for organic electronics. Its sister molecule perylene diimides (PDI) already successfully was used as NF acceptors for OSCs. However, using PMI for NF acceptors are rarely reported presumably due to the difficulty of large-scale synthesis. , But PMI also possesses strong light absorption ability and good photostability; in particular, it has a higher-lying lowest unoccupied molecular orbital (LUMO) compared to PDI, which could be good for high V oc of OSCs. , For PMI NF candidates, the linker group between two PMI greatly tailor the comprehensive properties of NF acceptors. Regular bridge units such as thiophene or benzyl or other aryl group-linked A–D–A type (A = PMI) NF shows poor photovoltaic performance .…”
Section: Introductionmentioning
confidence: 99%